Comparison of Conventional and Modified Burners in Performance with Different Fuels using a Linear and a Non-linear Eddy-viscosity Turbulence Model - ÇİFTÇİOĞLU, GÖKÇEN ALEV; YANGAZ, MURAT UMUT (ISFAHAN UNIV TECHNOLOGY, 2019)
Energy sources must be used efficiently to provide the sufficient amount of energy for the still-growing population in the world, already threatened by the effects of global warming. The significant increase in the use of natural resources causes serious problems due to its unsustainable situation. Therefore, exhaust gases/emissions must be reduced to prevent more damage on the environment. This study aims to provide solutions for a sustainable ecosystem by lowering emissions such as CO, unburnt HC, NOx, and enhancing the combustion efficiency in a certain type/scale industrial burner. In that way, some geometric modifications (on furnace design and the connected burner) have been applied on the conventional type burners to benefit the effects of preheating of combustion air. Modified geometries have been analyzed numerically and compared with the conventional design's results. Moreover, the comparison between a linear and non-linear turbulence model has been given in terms of simulation results. Major findings indicate that Burner-1 has significantly lower emissions compared to the others. Preheating effect coupled with the flue gas recirculation (FGR) seems to work well in terms of performance and emissions. Also, a significant difference between linear and non-linear turbulence model appeared on the emission characteristics for the same simulations.
Keywords: Computational fluid dynamics; Combustion; Preheating; Emissions; Flue gas recirculation; NUMERICAL-SIMULATION; FLAME CHARACTERISTICS; COMBUSTION; SWIRL; EMISSION; FLOW; OPTIMIZATION; BIOGAS